Perspective on the development of XPS and the pioneers who made it possible - D. R. Baer; P. M. A. Sherwood (Frontiers in Analytical Science)
As of 2024, the use of X-photoelectron spectroscopy (XPS), initially called Electron Spectroscopy for Chemical Analysis (ESCA), has grown to become the most widely used surface analysis method. In this paper we offer a perspective of the early development of XPS and describe some of the advances and pioneers who made them that provided the foundation for it to grow into the technique we know today. Included is information about the early development of photoelectron spectroscopy, the seminal work of Kai Siegbahn, influential conferences that helped spread excitement and provide a fundamental understanding of the method, early development of commercial instruments, and identification of the need for systematic metrology. Because hundreds of researchers have contributed to advancing the method, we note that this is our perspective, with likely a different emphasis than others may have chosen. To limit the scope somewhat, we have chosen to focus on authors whose contributions started before 1980.